Non‐traumatic musculoskeletal pain in Western Australian hospital emergency departments: A clinical audit of the prevalence, management practices and evidence‐to‐practice gaps. (14th May 2019) - Baker, Briarley; Kessler, Kenny; Kaiser, Bronwyn; Waller, Robert; Ingle, Michael; Brambilla, Simone; Viscardi, Elena; Richards, Karen; O'Sullivan, Peter; Goucke, Roger; Smith, Anne; Yao, Felix; et al.
Abstract: Objectives: Musculoskeletal pain (MSP) conditions are a leading cause of morbidity worldwide and a common reason for ED presentation. Little is currently known about non‐traumatic MSP (NTMSP) presenting to EDs. The present study described the prevalence and management practices of NTMSP in EDs. Methods: The design was a retrospective clinical audit in two hospital EDs in Western Australia covering 3 months beginning 1 January 2016. We defined NTMSP as pain of musculoskeletal origin occurring in the absence of external force or excessive physical loading. The outcomes measured included: patient, condition and hospital‐episode characteristics, as well as management practices. Management practices were compared to recommended care derived from guideline recommendations. These included: assessment for red flags and psychosocial risk factors, appropriate use of diagnostic imaging, provision of patient education, administration and prescription of analgesic medication, and assessment of risk factors for opioid‐related harm. Results: Eight hundred and eighty‐eight patients were included in the present study. NTMSP accounted for 3.0% of all ED presentations. According to clinician documentation, red flag and psychosocial assessments were recorded in 73.3 and 10.5% of patients. Forty‐one percent of patients were referred for imaging, of which 39.7% were inconsistent with guideline recommendations. Education was recorded 52.0% of the time. At least one opioid medication was administered to 55.3% of patients and there was no documented assessment of risk factors for opioid‐related harm. Conclusions: NTMSP is a relatively common reason for ED presentation. Documented management practices are discordant with guideline recommendations. Strategies to improve the concordance between management and guideline recommendations are needed.